Hubungan Kreativitas dengan Hasil Belajar Bahasa Indonesia - Olin Nita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to describe creativity with the learning outcomes of Indonesian students in class X SMAN 4 Payakumbuh. The method used was the correlation method. Determination of the sample is done by cluster random sampling or randomly, then which amaunted to 20 students. The results found that there was a significant relationship between student learning creativity and Indonesian language learning outcomes because the results of hypothesis testing proved that tcount was greater than ttable namely, 4.244> 1.734. Conclusion, there is a significant relationship between learning creativity with Indonesian language learning outcomes Keywords: Creativity, Learning Outcomes